Mengintegrasikan kegiatan literasi dengan keterampilan berbicara siswa SDN 2 Tanjungsari Kabupaten Tulungagung - Inne Arummaisha Chairani; Bagas Aldi Pratama (Nur Science Institute, 2026)
This study aims to analyze the application of the storytelling method in improving the literacy skills of third-grade students at SDN 2 Tanjungsari, Boyolangu District, Tulungagung Regency. This study uses a descriptive qualitative approach with 42 students as research subjects. Data collection techniques were carried out through observation, interviews, and documentation of activities. The storytelling method was applied through activities such as listening to stories with contextual themes, rewriting the content of the stories, and reading the results aloud in front of the class. The results of the study showed positive developments in students' literacy skills, including reading, writing, and speaking. Students were able to construct simple sentences more coherently, showed increased confidence in reading their writing, and participated more actively in speaking activities. However, there were still obstacles in the form of spelling errors, varying reading fluency, and limited vocabulary in some students. Overall, the storytelling method proved to be effective as a contextual and enjoyable integrated literacy learning approach for elementary school students, especially in lower grades. This method can be applied in long-term learning as a more innovative, creative, and student-centered learning approach.